PSA secretion and cell proliferation are affected by NCoR1 silencing in prostate cancer cells - Costa, Bruna Pasqualotto; Brum, Ilma Simoni; Pizzolato, Lolita Schneider; Biolchi, Vanderlei; Branchini, Gisele (Clinical and Biomedical Research, 2020)
The androgen receptor (AR) plays an important role in normal prostate gland development as well as in prostatic neoplasms. Transcriptional regulation by AR is modulated by its interaction with co-activators or co-repressors, such as NCoR1 (nuclear receptor co-repressor 1), which is involved in the reduction of AR activity over the target gene transcription. To identify the role of NCoR1 in the prostate cancer androgen independence in a cell line model, we aimed to evaluate the effects of silencing NCoR1 on prostate-specific antigen (PSA) gene expression, the proliferative response and PSA secretion on the supernatant of C4-2B and LNCaP cells that were submitted to small interfering RNAs (siRNAs) transfection and to treatments with different androgen dosages. In LNCaP and C4-2B cells with no dihydrotestosterone (DHT) treatment, a decrease of PSA mRNA expression was observed 48 hours and 72 hours after gene silencing in the siNCoR group when compared to the control and siNC groups. LNCaP and C4-2B cells showed a biphasic pattern in response to dihydrotestosterone treatment in transfected groups (siNCoR and siNC) as well as in the control condition (no transfection). The secretion of PSA in cell supernatant of LNCaP and C4-2B cells was higher in the siNCoR group, and, regarding the hormonal treatment, higher in the 10-8 M DHT group. A reduction in the levels of NCoR1 seems to have a double influence on the activity of AR in PCa cells. These results suggest that NCoR can act as AR a co-repressor depending upon hormonal stimulation.